2013
DOI: 10.3389/fpsyt.2013.00171
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity: Translating the Potential

Abstract: The mismatch negativity (MMN) component of the auditory event-related potential has become a valuable tool in cognitive neuroscience. Its reduced size in persons with schizophrenia is of unknown origin but theories proposed include links to problems in experience-dependent plasticity reliant on N-methyl-d-aspartate glutamate receptors. In this review we address the utility of this tool in revealing the nature and time course of problems in perceptual inference in this illness together with its potential for us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
105
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 198 publications
(254 reference statements)
4
105
0
Order By: Relevance
“…This is well in line with deficits in auditory MMN which have been widely explored for more than three decades, and since the first report of an aMMN deficit (Shelley et al, 1991), there have been 256 articles published addressing this issue (source PubMed, "MMN" schizophrenia, May 2015). Most of these studies showed an aMMN amplitude reduction in schizophrenia (Todd, Michie, Schall, Ward, & Catts, 2012;Umbricht & Krljes, 2005) and, moreover, this sensory deficit was associated with the impaired daily functioning of the patients (Todd, Harms, Schall, & Michie, 2013). The aMMN sensitivity to the sensory deficit depends on the type of deviance used, e.g., pitch, intensity, or duration, with the duration violation being the most sensitive test as shown by a meta-analysis of 32 reports (Umbricht & Krljes, 2005).…”
Section: Summary Of Vmmn Studies In Schizophreniamentioning
confidence: 99%
“…This is well in line with deficits in auditory MMN which have been widely explored for more than three decades, and since the first report of an aMMN deficit (Shelley et al, 1991), there have been 256 articles published addressing this issue (source PubMed, "MMN" schizophrenia, May 2015). Most of these studies showed an aMMN amplitude reduction in schizophrenia (Todd, Michie, Schall, Ward, & Catts, 2012;Umbricht & Krljes, 2005) and, moreover, this sensory deficit was associated with the impaired daily functioning of the patients (Todd, Harms, Schall, & Michie, 2013). The aMMN sensitivity to the sensory deficit depends on the type of deviance used, e.g., pitch, intensity, or duration, with the duration violation being the most sensitive test as shown by a meta-analysis of 32 reports (Umbricht & Krljes, 2005).…”
Section: Summary Of Vmmn Studies In Schizophreniamentioning
confidence: 99%
“…A recent review (Todd et al 2013) recommended the intensive use of MMN in translational studies as means of investigating the pathophysiology of schizophrenia. Nevertheless, it has also been argued that future research on MMN in schizophrenia would benefit from the use of more sophisticated paradigms than the typical oddball paradigm (Umbricht and Krljes 2005).…”
Section: "State Of the Art" -Mmn In Schizophreniamentioning
confidence: 99%
“…It should be noted, however, that a recent metaanalysis suggested that duration MMN was also affected by normal aging in non-psychiatric populations (Cheng et al 2013b). It has also been argued that all MMN paradigms rely on a similar neuronal mechanism and that use of different stimulation modes and formats might be an obstacle to comparative analysis (Todd et al 2013).…”
Section: Beyond Duration and Frequency Deviantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research topic also highlights the significance of the N -methyl-d-aspartate receptor for the development of psychosis and how glutamatergic metabolites are related to symptoms and cognitive function in clinical samples, suggesting promising new target pathways for the treatment of psychosis (10)(11)(12). Furthermore, electrophysiological modeling strategies in animals (13) and healthy subjects (14)(15)(16) are presented, which might help to establish neurobiological markers not only for the treatment of cognitive deficits but also for the prediction of psychosis and the development of preventive treatment schemes. The largest part of this issue unifies theoretical and experimental evidence reflecting the immense potential of computational neuroscience for shedding new light on the neurophysiological mechanisms underlying psychosis in general and on the formation of specific psychopathological signs and symptoms in particular.…”
mentioning
confidence: 98%